Official Correction 130: Official Correction 130 (Opinion 2407) – Entry on Official List of Specific Names in Zoology amended - Nomenclature, International Commission on Zoological (Bulletin of Zoological Nomenclature, 2018)
Published BZN 75 (31 December 2018): 300.